IMPLEMENTATION OF SCHOOL PROGRAMS AT POPULATION IN LEARNING (Case Study in South Bengkulu 1 High School) - Sarifah Aini; Bambang Sahono (UNIB Press, 2019)
This study aims to describe the implementation of the Population Alert School (SSK) in SMAN 1 South Bengkulu. The method used is descriptive qualitative. The informants of this study were 13 people involved in the SSK program. Data collection techniques are interviews, observation, and documentation. Data analysis techniques involve the stages of data collection, data reduction, data presentation and drawing conclusions. Based on the field findings it can be concluded that the results of the study are: (1) SMAN 1 South Bengkulu has prepared a policy foundation in the form of a written decree, financial support, facilities and infrastructure, human resources preparation by including teachers in SSK training. (2) The execution of PBM is in accordance with the RPP by the incorporation of 8 family functions material, visits to agencies related to SSK, students have been able to integrate SSK material with the ability to analyze population data and population problems, as well as the presence of students' understanding about quality families and early-age marriages. (3) The evaluation of SSK implementation shows that the school has a Population Corner, the values of eight family functions are internalized in students, students have understood about reproductive health, maturation of marital age and the importance of quality family. (4) There are obstacles in activities such as: lack of funds for activities and infrastructure, and not all activities can be integrated in the extracurricular subjects and activities, as well as limited documentation.